Land Subsidence Hazard Mapping in relation with Sinkholes in Saptosari District, Gunung Kidul, Indonesia - Fikrillah, R.R. (2022)
Saptosari is one of the areas in the karst terrain of Gunung Kidul Regency, Yogyakarta, Indonesia. In this area, sinkholes are very common, especially in weathered and covered by soil overburden. It is known a lot of land subsidence due to sinkholes are found and reported by the local community. Therefore, the purpose of this study was to map the land subsidence hazard zone due to the presence of sinkholes. To achieve this goal, field observations and evaluation of secondary data were carried out to collect slope data, lithology, lineament of geological structures, and the location of sinkholes and subsidence that already existed. Analytical Hierarchy Process (AHP) was carried out to determine the weight of the geomorphological parameter, lithological parameter, and the distance to geological structure in order to predict the occurrence of sinkholes. The weighted results of the AHP method are then used to create a land subsidence hazard map by using the GIS-overlay method. The study reveals three subsidence hazard zones in the research area, namely (1) high susceptible area with subsidence probability of 92, (2) moderate susceptible area with subsidence probability of 4.7, and (3) low susceptible area zones with 0 of subsidence probability. © Published under licence by IOP Publishing Ltd.